Cementless humeral head resurfacing for degenerative glenohumeral osteoarthritis fails at a high rate - Maier, Michael Wolfgang; Hetto, Pit; Raiss, Patric; Klotz, Matthias C. M.; Bülhoff, Matthias; Spranz, David Maximilian; Zeifang, Felix (Journal of orthopaedics, 2018)
Purpose - The aim of the study was to examine clinical and radiographic results of a cementless humeral surface and to evaluate prognostic parameters for implant failure. - Methods - 34 shoulders were examined preoperatively and after a mean 2.7 years. Radiographic parameters, Constant scores (CS) and complications were recorded. - Results - The mean CS improved from 27 to 51 points. Eight patients (24%) had an implant revision for secondary glenoid erosion. In the revision group was an increase of the LGHO of 8.4%. - Conclusions - The study shows a high revision-rate (24%). Predictor for an implant failure was an operative changing of the LGHO.
Available online 21 February 2018
Gesehen am 18.09.2019